Interactive Ecosystem Simulator - ATTERFORS, JOHAN; HOLMBERG, CARL; HUANG, ALEXANDER; KARHU, ROBIN; LAE, BRAGE; LARSSON VAHLBERG, ALEXANDER (My University, 2021)
As ecosystems are complex domains, both analytical and computer-aided models can aid in gaining insights about their dynamics. One such computer-aided model is the concept of ecosystem simulation. This project aims to build an interactive and visual ecosystem simulation in the Unity game engine. The purpose is to explore how modelling of animal behavior, trait evolution and dynamic terrain can be combined with a graphical representation to create an interactive ecosystem simulator. Implementation of these aspects includes exploration of machine learning and reactive behavior for animals, terrain generation, genetic reproductive algorithms as well as run-time visualization and collection of data. The effects of these aspects are evaluated using comparisons between animal behavior models, impact of terrain and outcomes of genetic evolution, in addition to software interactivity. The outcome of this project indicated that the machine learning prioritization animals performed nearly as well as reactive rule based animals in terms of survival, while the machine learning steered animals performed sub-par in comparison to the others. Furthermore, it showed that terrain changes seemingly has a greater impact on the predator populations compared to the prey populations in the simulator. Additionally, as a result of the proposed evolution model, genetic traits of animals indicated to be potentially adaptive to the environment. Finally, the graphical representation provided visual feedback and information to users. In total, the final product resulted in a working interactive ecosystem simulator. The implications of this thesis offers a baseline framework for modelling a visual interactive ecosystem simulator in regards to future research, academic and entertainment applications.
Keywords: Ecosystem; Simulation; Unity; AI; ML; RL; ABM; GA; PCG; Welford